Who Buys Bitcoin? The Cultural Determinants of Bitcoin Activity - Foley, S; Frijns, B; Garel, A; Roh, TY (Elsevier BV, 2022)
We examine the relationship between national culture and a country's Bitcoin activity. Given that Bitcoin is a high-risk currency/investment that is frequently used for illegal purposes and whose market is relatively opaque, we focus on the cultural dimension of individualism, which has been related to financial market participation, risk-taking behavior, and overconfidence. Using unique data that includes the originating country for Bitcoin transactions, we examine the relationship between individualism and a country's Bitcoin activity for a sample of 80 countries between 2009 and 2020. We find a significant and positive relationship between a country's individualism and its use of Bitcoin consistent with cultural values affecting the demand for such high-risk currency/investments.
Keywords: 3502 Banking, Finance and Investment; 35 Commerce, Management, Tourism and Services; 1501 Accounting, Auditing and Accountability; 1502 Banking, Finance and Investment; 1801 Law; Finance; 3501 Accounting, auditing and accountability; 3502 Banking, finance and investment; 3801 Applied economics